ON tHE PROBLEM OF CALCULATION OF WATER RESOURcES of sMALL LOW-MOUNTAIN RIVERS - N.Z, Sagdeev; Kh, Yunusov G.; J.T, Khamzaeva (International Journal of Psychosocial Rehabilitation, 2020)
In the article preliminary and basic results on calculation of hydrological characteristics of small low-mountain rivers of Uzbekistan for the purpose of calculation of their water resources are presented.